Pengaruh Dualisme Sistem Hukum Nasional Dan Minimnya Ratifikasi Instrumen Internasional Terhadap Hambatan Penegakan Hukum Kejahatan Perdagangan Manusia Lintas Negara - Gema Fajar Fitriansyah; Wefy Efticha Sary; Dwi Putri Lestarika (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines how legal dualism and the lack of ratification of international instruments hinder the enforcement of cross-border human trafficking laws in Indonesia. Using a normative juridical method, the research analyzes national regulations and international instruments such as the Palermo Protocol and ACTIP. The findings reveal that legal dualism creates misalignment between domestic and international laws, obstructing cross-border cooperation, extradition, mutual legal assistance, and victim protection. The limited ratification of international instruments weakens Indonesia’s position in transnational collaboration. The study recommends harmonizing domestic laws, accelerating ratification, and strengthening law enforcement institutions to enhance the effectiveness of combating human trafficking.